2011
DOI: 10.1186/2046-1682-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Stability of double-stranded oligonucleotide DNA with a bulged loop: a microarray study

Abstract: BackgroundDNA is a carrier of biological information. The hybridization process, the formation of the DNA double-helix from single-strands with complementary sequences, is important for all living cells. DNA microarrays, among other biotechnologies such as PCR, rely on DNA hybridization. However, to date the thermodynamics of hybridization is only partly understood. Here we address, experimentally and theoretically, the hybridization of oligonucleotide strands of unequal lengths, which form a bulged loop upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…There has been considerable attention in recent years [9,22,[24][25][26][27][28][29][30][31][32][33][34] in understanding the fundamentals of hybridization in DNA microarrays and its impact in data analysis. Here, we have shown that microarrays are a reliable and high-throughput tool to gain insight on DNA hybridization thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable attention in recent years [9,22,[24][25][26][27][28][29][30][31][32][33][34] in understanding the fundamentals of hybridization in DNA microarrays and its impact in data analysis. Here, we have shown that microarrays are a reliable and high-throughput tool to gain insight on DNA hybridization thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…A more general (and precise) model would describe the invading protein through a binding energy ε ′ different from the binding energy ε for the bound protein in case of heterogeneous replacement, as well through its number of bound units, rather than the on/off description used here. Binding/unbinding of small DNA fragments (oligonucleotide) on a DNA under force [11] and exchange of DNA-binding oligonucleotides in DNA hybridization assays [9, 13, 14] are likely described by the Z-S-SB model. Including sequence specificity (dependence of ε on the sites) could help in modeling such experiments [12].…”
mentioning
confidence: 99%
“…To get a better insight into the hybridization process of two strands of unequal length, Trapp et al considered a DNA microarray with additional bases in the probe sequence motifs (54). The target solution contains only one target species of a specific length.…”
Section: Dna Arrays From First Principlesmentioning
confidence: 99%
“…Taking into account unavoidable sequence defects, the model can reproduce our data well. Details can be found in (54).
Figure 6.Averaged signal intensity over loop length (top) and loop position (bottom).
Figure 7.Comparison between the experimental data and the model.
…”
Section: Dna Arrays From First Principlesmentioning
confidence: 99%